The Comparison of %Ejection Fraction Between 4D MSPECT and Myometrix in Gated Myocardial SPECT: The Comparison of %Ejection Fraction Between 4D MSPECT and Myometrix in Gated Myocardial SPECT - Narawong, Taratip (The ASEAN Journal of Radiology, 2025)
Objective: To compare the %Ejection Fraction (%EF) between 4D MSPECT and Myometrix software in Gated Myocardial SPECT for a one day protocol study in Rajavithi hospital. Materials and Methods: The 100 retrospective data of the Gated Myocardial SPECT from the suspected Coronary Artery Disease patients during July to October 20111 was reanalyzed by an experienced operator. Two software ie, 4D MSPECT and Myometrix were used. The reconstruction parameters for rest study was OSEM/MLEM 2 iterations 10 subsets with no attenuation correction and the post fiter of 30 Butterworth at critical frequency of 0.548 power 12.6. The reconstruction paramefers for stress study was OSEM/ MLEM 2 iterations 10 subsets and the post filter of 3D Buttenworth at critical frequency 0 45 power 10. The %EF, end diastolic volume (EDV) and end systolic volume (ESV) were compared between each software. A two tailed pair t-test was used to test the statistically signticant diference in these three value for both intraoperator and interoperator studies. Results: The average age of the patient was 63.9+12.1 (mean+SD) with 44 female and 56 male. In intraoperator study, the mean %EF of 4DMSPECT showed the good correlation with Myometrix for both rest and stress study (r-0 95 and r=0.96, respectively.) In interoperator study, the mean 9EF of 4DMSPECT also gave the good correlation with Myometrix for both rest and stress study (r=0.99 and r=0.99.99, respectively. The statistical test between two software showed no significant difference. (p>0.05). Conclusion: The SEF from both software gave the good correlation. Since these two software packages used different algorithm so it did not recommend to interchange between these two software.